264-3x=42x+19

Simple and best practice solution for 264-3x=42x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 264-3x=42x+19 equation:


Simplifying
264 + -3x = 42x + 19

Reorder the terms:
264 + -3x = 19 + 42x

Solving
264 + -3x = 19 + 42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42x' to each side of the equation.
264 + -3x + -42x = 19 + 42x + -42x

Combine like terms: -3x + -42x = -45x
264 + -45x = 19 + 42x + -42x

Combine like terms: 42x + -42x = 0
264 + -45x = 19 + 0
264 + -45x = 19

Add '-264' to each side of the equation.
264 + -264 + -45x = 19 + -264

Combine like terms: 264 + -264 = 0
0 + -45x = 19 + -264
-45x = 19 + -264

Combine like terms: 19 + -264 = -245
-45x = -245

Divide each side by '-45'.
x = 5.444444444

Simplifying
x = 5.444444444

See similar equations:

| -36x^4+25x^3-4= | | h+(-9)=-9 | | (x^4)+(4x^2)+400=0 | | 15t+9=5t+9 | | 5b-12=14 | | 9(x-4)=72 | | -10y-7=6y+9 | | d-15=44 | | -441=4(-8n-4) | | 2(8x+2)=3(2x-7) | | 5x+2x=6x-2 | | 5x-6(3x+4)=9(x-6)+3 | | -9x+4x+15-10x= | | 7u^2-48u-7=0 | | 0.02-0.02(x+2)=-0.04(2-x) | | 6x+6=4x+2 | | 4-(3.5x+2)=x-7 | | 10y-7-6y+9= | | 125x^3-8= | | -10y-7-6y+9= | | 5[15x+25]=950 | | 3x^2-4x-9=0 | | 3x^5-6x^3+11x^2-10=0 | | x+x+9=95 | | 3(x-2)+x+4=2(x-1) | | 2(1-11n)+11=-8(n+1)-7 | | -4x+7=27 | | -2a+40+9a=4a-7a | | x^2*5y^4= | | 4(3y+-1)+13=5y+2 | | 6b=6 | | x^2*5y^2= |

Equations solver categories